Glulam bonding quality of chromated copper arsenate treatment applied to Pinus elliottii wood and three structural adhesives - Bianchi, Natália Andrade [UNESP]; de Moraes, Matheus Henrique Morato; de Oliveira, Karina Aparecida [UNESP]; de Oliveira, Carolina Aparecida Barros [UNESP]; Molina, Júlio Cesar; Christoforo, André Luis (Universidad del Bio Bio, 2025)
Glued laminated timber is an alternative gaining prominence in the Brazilian construction field. As a result, industries seek ways to improve the quality of their products, focusing on the wood used, the adhesive, and the manufacturing process. The aims of this study are to evaluate the effect of the preservative treatment chromated copper arsenate (CCA) as a preservative treatment on the gluing quality of Pinus elliottii (slash pine) glued laminated timber (Glulam) elements. For this purpose, Glulam was compared with and without CCA treatment, using Cascophen RS 216-M, Jowat 686,60 and AG 101 adhesives to bond the laminated wood specimens. The glue quality was evaluated through delamination and shear strength tests of the glue lines based on the test method, following the European standard. The delamination results indicated that there were no significant differences between those obtained for the combinations of wood treated with CCA and wood in natura. The results of the shear tests on the glue lines revealed significant differences when comparing the performance of wood treated with CCA to that of untreated (in natura) wood. Specifically, when using Cascophen 216-M and polyurethane AG 101 adhesives, the treated wood demonstrated notably different shear strengths. This indicates that the preservative treatment with chromated copper arsenate alters the bonding effectiveness of these adhesives, highlighting the importance of selecting appropriate adhesive formulations for treated wood to ensure optimal bonding quality. The only species/adhesive combination that showed a delamination limit lower than 4 % was the one that considered natural wood glued with Cascophen 216-M adhesive. To confirm these results is essential a complementary study evaluating the viscosity of the resins used.
Keywords: Adhesive bonding; chromated copper arsenate; delamination; glue line shear; glued laminated timber; Pinus elliottii; preservative treatment